DMAI-driven all-inorganic antimony-based perovskite-inspired solar cells with record open-circuit voltage. Issue 12 (6th March 2023) - Guo, Yixin; Zhao, Fei; Yang, Peizhi; Gao, Minjie; Shen, Junhao; Tao, Jiahua; Jiang, Jinchun; Chu, Junhao
Abstract : In this work, low-cost inorganic antimony-based perovskite-inspired solar cells with the co-assistance of DMAI and RbCl are constructed. The resulting device achieves a relatively high efficiency of 3.37% with a record open-circuit voltage of 0.93 V. Abstract : The emergence of all-inorganic antimony (Sb)-based perovskite-inspired solar cells (PISCs) has attracted much attention due to their good stability and non-toxicity compared with lead (Pb)-based perovskite solar cells (PSCs). However, it is still a great challenge to develop a simple, highly repeatable, and anti-solvent-free strategy to obtain high-quality all-inorganic Sb-based perovskite-inspired films due to their quick formation and anisotropic growth. Herein, the precursor solution is supplemented with dimethylammonium iodide (DMAI) as a novel and low-cost additive to help control the nucleation and growth process. The volatile DMAI additive could significantly boost the formation of a mix-oriented intermediate 0D phase, leading to smooth and compact Sb-based perovskite-inspired films with low defect concentration and optimized crystal orientation. Additionally, the interface diffusion brought on by rubidium chloride (RbCl) treatment could effectively suppress the low-dimension impurity phase and promote a better band alignment. As a reward, the power conversion efficiency (PCE) of the champion device can reach 3.37% with a superior open-circuit voltage ( V oc ) of 0.93 V, which is the record PCE value for Sb-based PISCs hitherto. This work will provide a fresh and inspiring way to realize highly efficient lead-free PISCs.